EFFECT OF PRESSURE ON THE LIGHT ABSORPTION COEFFICIENT OF GaAs (Universal International Scientific Journal, 2026)
This paper theoretically analyzes the effect of external pressure on the light absorption coefficient in semiconductor materials. The state of energy bands and the change in the band gap width as a result of changes in the crystal lattice parameters under pressure are considered. Based on the relationship between the light absorption process and the band structure, the dependence of the absorption coefficient on the photon energy is analyzed. Theoretical models explain how the shift of energy bands under pressure directly affects the energy of transitions. Also, the possibilities of determining the dependence of the band gap width on pressure through the shift of the absorption spectrum are shown. The obtained theoretical results are of great importance in terms of controlling the optical properties of semiconductor materials and their application in optoelectronic devices.
Keywords: energy band position; forbidden band width; effective mass values